Marine insurance fraud - Soyer, Bariş (Maritime and transport law library, 2014)
This book provides a comprehensive and coherent legal analysis of the impact of fraud on the position of various parties to a marine insurance contract, as well as the cover provided by standard marine policies. The issues under discussion in this invaluable guide are also equally relevant in the context of non-marine insurance contracts.